Development of microwave and soft X-ray sources based on coherent radiation and Thomson scattering; Journal of Physics: Conference Series; Vol. 236, Iss. 1 - Aryshev A.; Araki A.; Fukuda M.; Karataev P. V. Pavel Vladimirovich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sakaue K.; Sukhikh L. G. Leonid Grigorievich; Urakawa J.; Verigin D. A. Dan Aleksandrovich (2010, 2010)
Title screen